The influence of delivery vectors on HIV vaccine efficacy - Ondondo, Beatrice O. (Frontiers in Microbiology, 2014)
Development of an effective HIV/AIDS vaccine remains a big challenge, largely due to the enormous HIV diversity which propels immune escape. Thus novel vaccine strategies are targeting multiple variants of conserved antibody and T cell epitopic regions which would incur a huge fitness cost to the virus in the event of mutational escape. Besides immunogen design, the delivery modality is critical for vaccine potency and efficacy, and should be carefully selected in order to not only maximise transgene expression, but to also enhance the immuno-stimulatory potential to activate innate and adaptive immune systems. To date, five HIV vaccine candidates have been evaluated for efficacy and protection from acquisition was only achieved in a small proportion of vaccinees in the RV144 study which used a canarypox vector for delivery. Conversely, in the STEP study (HVTN 502) where human adenovirus serotype 5 (Ad5) was used, strong immune responses were induced but vaccination was more associated with increased risk of HIV acquisition than protection in vaccinees with pre-existing Ad5 immunity. The possibility that pre-existing immunity to a highly promising delivery vector may alter the natural course of HIV to increase acquisition risk is quite worrisome and a huge setback for HIV vaccine development. Thus, HIV vaccine development efforts are now geared towards delivery platforms which attain superior immunogenicity while concurrently limiting potential catastrophic effects likely to arise from pre-existing immunity or vector-related immuno-modulation. However, it still remains unclear whether it is poor immunogenicity of HIV antigens or substandard immunological potency of the safer delivery vectors that has limited the success of HIV vaccines. This article discusses some of the promising delivery vectors to be harnessed for improved HIV vaccine efficacy.